Screening for potential hazard effects from four nitramines on human eye and skin - Fjellsbø, Lise Marie; Van Rompay, An R.; Hooyberghs, Jef; Nelissen, Inge; Dusinska, Maria (Toxicology in vitro, 2013)
► Four nitramines were investigated for toxic effects on in vitro skin and eye models. ► 2-Methyl-2-(nitroamino)-1-propanol, methyl- and ethanolnitramine were very severe irritants to eye. ► Dimethylnitramine was observed to be a mild eye irritant. ► Methyl- and ethanolnitramine were tested for skin sensitisation with no effect. ► None of the four tested nitramines were irritant or corrosive to skin. Amines have potential to be used in CO2 capture and storage (CCS) technology, but as they can be released into the environment and be degraded into more toxic compounds, such as nitrosamines and nitramines, there have been concerns about their negative impact on human health. We investigated the potential toxic effects from acute exposure to dimethylnitramine (DMA–NO2), methylnitramine (MA-NO2), ethanolnitramine (MEA-NO2) and 2-methyl-2-(nitroamino)-1-propanol (AMP-NO2). The eye irritation, and skin sensitization, irritation and corrosion potential of these substances have been evaluated in vitro using the Bovine Corneal Opacity and Permeability (BCOP) assay, VITOSENS® assay, Reconstructed Human Epidermis (RHE) skin irritation test and Corrositex Skin corrosion test, respectively. Exposure to DMA–NO2 induced a mild eye irritation response, while MA-NO2, MEA-NO2 and AMP-NO2 were shown to be very severe eye irritants. MA-NO2 and MEA-NO2 were tested for skin sensitization and found to be non-sensitizers to the skin. In addition, none of the four test substances was irritant or corrosive to the skin.